Kepemilikan Asing, Afiliasi Grup Bisnis, dan Kinerja Perusahaan - Pramesti Putri Ismayadewi; Noorlaily Fitdiarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study is aim to determine the effect of foreign ownership that moderated by business group affiliation on firm performance in Indonesia. This study uses multiple linear regression analysis with 269 samples of manufacturing listed firm on Indonesia Stock Exchange during 2011-2017. The independent variable of this study is foreign ownership, the dependent variable is firm performance measured by ROA, the moderating variable is business group affiliation and the control variables are age, size and leverage. The results shows that foreign ownership has a positive and significant effect on firm performance and business group affiliation weakened the positive effect of foreign institutional on firm performance.